(untitled) - European Trade Union Institute (ETUI) (SEER Journal for Labour and Social Affairs in Eastern Europe, 2008)
SEER tries t o stimulate the exchange of information among researchers, trade unionists and people who have a special interest in the political, social and economic development of the region of south-east Europe. The journal tries to draw attention to new research results and the latest analyses about the ongoing process of political and social changes in the south-east of Europe. It tries to create more understanding for the importance of the elaboration of democratic structures in industrial relations. The SEER combines contributions from different disciplines and »political schools« into an information package of interest for policy makers, researchers, academics and trade unionists from various backgrounds.  Website: www.seer.nomos.de